2006
DOI: 10.1021/es061248c
|View full text |Cite
|
Sign up to set email alerts
|

Passive Partitioning of Polychlorinated Biphenyls between Seawater and Zooplankton, a Study Comparing Observed Field Distributions to Equilibrium Sorption Experiments

Abstract: From previous studies, it remains unclear whether polychlorinated biphenyls (PCBs) are biomagnified in zooplankton or if concentrations are simply governed by passive partitioning. In this study, in the Gullmar Fjord on the Swedish west coast, field-determined lipid-normalized partition coefficients (log Klip) were compared to equilibrium partition coefficients from laboratory sorption experiments with dead and preserved zooplankton. There was no significant difference between the linear regressions of log Kli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 36 publications
5
23
2
Order By: Relevance
“…Several processes (e.g. exchange with water through passive partitioning, ingestion of contaminated food, and production of fecal pellets and eggs), occurring simultaneously, may affect the final body burden of PAHs derived from oil spills [Sobek et al, 2006;Berrojalbiz et al, 2011]. Moreover, all of these processes may vary as a function of ambient temperature and seasonality [Hallanger et al, 2011b].…”
Section: Resultsmentioning
confidence: 99%
“…Several processes (e.g. exchange with water through passive partitioning, ingestion of contaminated food, and production of fecal pellets and eggs), occurring simultaneously, may affect the final body burden of PAHs derived from oil spills [Sobek et al, 2006;Berrojalbiz et al, 2011]. Moreover, all of these processes may vary as a function of ambient temperature and seasonality [Hallanger et al, 2011b].…”
Section: Resultsmentioning
confidence: 99%
“…Based on empirical studies, passive partitioning between seawater and zooplankton is the controlling factor for HOC concentrations in zooplankton [12,13]. Furthermore, these studies concluded that biomagnification does not occur in zooplankton, because no increase in HOC concentrations with increasing trophic positions was observed [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these studies concluded that biomagnification does not occur in zooplankton, because no increase in HOC concentrations with increasing trophic positions was observed [12][13][14]. Trophic positions are calculated from the ratio of heavier to lighter stable isotope of nitrogen ( [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations